Crystallization and X‐ray diffraction studies of a two‐domain laccase from Streptomyces griseoflavus. Issue 9 (1st September 2015) - Tishchenko, Svetlana; Gabdulkhakov, Azat; Trubitsina, Liubov; Lisov, Alexander; Zakharova, Marina; Leontievsky, Alexey
<x xml:space="preserve">Abstract</x> Laccase (EC 1.10.3.2) is one of the most common copper‐containing oxidases; it is found in many organisms and catalyzes the oxidation of primarily phenolic compounds by oxygen. Two‐domain laccases have unusual thermostability, resistance to inhibitors and an alkaline optimum of activity. The causes of these properties in two‐domain laccases are poorly understood. A recombinant two‐domain laccase (SgfSL) was cloned from the genome of Streptomyces griseoflavus Ac‐993, expressed in Escherichia coli and purified to homogeneity. The crystals of SgfSL belonged to the monoclinic space group P21, with unit‐cell parameters a = 74.64, b = 94.72, c = 117.40 Å, β = 90.672°, and diffraction data were collected to 2.0 Å resolution using a synchrotron‐radiation source. Two functional trimers per asymmetric unit correspond to a Matthews coefficient of 1.99 Å3 Da−1 according to the monomer molecular weight of 35.6 kDa.